2022
DOI: 10.3389/fpsyg.2022.811282
|View full text |Cite
|
Sign up to set email alerts
|

The Nexuses Between Social Media Marketing Activities and Consumers’ Engagement Behaviour: A Two-Wave Time-Lagged Study

Abstract: This study examined how social media marketing activities (SMMA) influence consumers’ engagement behaviour in developing countries. Based on the stimulus-organism-response theory, we examined the effect of SMMA on consumers’ engagement intention and further investigated the moderating effect of social media sales intensity. The study employed a time-lagged design with two waves to confirm the hypothesised framework. The study findings showed that SMMA positively influence consumers’ engagement intention and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 138 publications
(148 reference statements)
2
10
0
Order By: Relevance
“…The first factor accounted for 17.527% of the variance, signifying that CMB was unlikely to be a problem in our survey (Yu et al. , 2021; Shang et al. , 2022; Ullah et al.…”
Section: Methodsmentioning
confidence: 93%
“…The first factor accounted for 17.527% of the variance, signifying that CMB was unlikely to be a problem in our survey (Yu et al. , 2021; Shang et al. , 2022; Ullah et al.…”
Section: Methodsmentioning
confidence: 93%
“…Two waves of data collection at the two-month interval were conducted to avoid common method bias (Podsakoff et al. , 2003; Shang et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, before recording their final response, participants can assess and act on their behavior using this approach (Mehmood et al, 2021a,b). Two waves of data collection at the two-month interval were conducted to avoid common method bias (Podsakoff et al, 2003;Shang et al, 2022).…”
Section: Employees' Passion and Work-related Outcomesmentioning
confidence: 99%
“…Likewise, Sharma et al (2020) demonstrated that quality relationships, including trust, satisfaction, and commitment positively impact consumer purchase intentions toward fashion apparel products in the Indian context. Similarly, Sohaib (2022) revealed that relationship quality factors such as, commitment, trust, and satisfaction significantly increase customer repurchase intentions in the banking sector of Pakistan. In general, it is believed that a relationship's (or its constituents') high quality results in a proportionally high level of purchase intention (Kuo et al, 2009;Hajli, 2014a).…”
Section: Relationship Quality (Commitment Trust and Satisfaction) And...mentioning
confidence: 97%